A comprehensive high-resolution targeted workflow for the deep profiling of sphingolipids - Peng, Bing; Sharma, Rakesh; Tews, Björn (Analytical chemistry, 2017)
Sphingolipids make up a highly diverse group of biomolecules that not only are membrane components but also are involved in various cellular functions such as signaling and protein sorting. To obtain a quantitative view of the sphingolipidome, sensitive, accurate, and comprehensive methods are needed. Here, we present a targeted reversed-phase liquid chromatography-high-resolution mass spectrometry-based workflow that significantly increases the accuracy of measured sphingolipids by resolving nearly isobaric and isobaric species; this is accomplished by a use of (i) an optimized extraction procedure, (ii) a segmented gradient, and (iii) parallel reaction monitoring of a sphingolipid specific fragmentation pattern. The workflow was benchmarked against an accepted sphingolipid model system, the RAW 264.7 cell line, and 61 sphingolipids were quantified over a dynamic range of 7 orders of magnitude, with detection limits in the low femtomole per milligram of protein level, making this workflow an extremely versatile tool for high-throughput sphingolipidomics.